2020
DOI: 10.1177/2150132720905950
|View full text |Cite
|
Sign up to set email alerts
|

Management of Restless Legs Syndrome in Pregnancy and Lactation

Abstract: Restless legs syndrome (RLS) affects about 20% of all pregnant women. RLS symptoms are usually moderate to severe in intensity during pregnancy and can result in insomnia, depression, and other adverse outcomes. Although iron deficiency has been implicated as a potential etiological factor, other mechanisms can also play a role. Nonpharmacologic methods are the primary recommended form of treatment for RLS in pregnancy and lactation. Iron supplementation may be considered when the serum ferritin is low; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
(144 reference statements)
0
4
0
2
Order By: Relevance
“…There are several hypotheses trying to establish an association between RLS and gestation. However, the pathophysiological mechanisms of this disorder in pregnancy are misunderstood and further investigations are required 1,12,13 . Hormonal changes, the metabolism of iron, ferritin and folate, vitamin D deficiency, genetic factors and variations in zinc and magnesium levels have been hypothesized 1,6,10,14 .…”
Section: Introductionmentioning
confidence: 99%
“…There are several hypotheses trying to establish an association between RLS and gestation. However, the pathophysiological mechanisms of this disorder in pregnancy are misunderstood and further investigations are required 1,12,13 . Hormonal changes, the metabolism of iron, ferritin and folate, vitamin D deficiency, genetic factors and variations in zinc and magnesium levels have been hypothesized 1,6,10,14 .…”
Section: Introductionmentioning
confidence: 99%
“…There was no statistically significant connection between RLS and the number of previous pregnancies in pregnant women observed [28]. RLS is a very common reason for insomnia in pregnancy [31]. Additionally, in comparison to the women without RLS, those affected by this disorder are more likely to have poor sleep quality, poor daytime function and excessive daytime sleepiness [32].…”
Section: Restless Leg Syndromementioning
confidence: 90%
“…Authors listed 5 treatment options that were found to be beneficial: moderate-intensity exercise, yoga, massage, sequential compression devices, avoidance of aggravating causes of RLS and treatment of obstructive sleep apnea. In iron deficiency, its supplementation should be also considered [31].…”
Section: Restless Leg Syndromementioning
confidence: 99%
“…임신이 진행됨에 따라 임부는 생리적 변화와 임신에 대한 양가감정, 전반적인 건강상태의 변화만이 아니라 분만 시 겪게 될 불안과 두려움에 의한 심리적 변화 등을 겪는다 [2]. 이러한 변화는 임신기간 동안 임부에게 스트레스로 작용하여 피로를 증가시키고, 부적절한 수면 또는 수면장애 증상을 초래하고, 하지불안증후군(Restless Legs Syndrome; 이후부터 RLS)의 증상이 나타나거나 심해진다 [3] [4].…”
Section: 서론unclassified
“…RLS는 수면을 방해하는 감각운동 신경장애 [3]로, 개인이 주관적으로 느끼는 다리나 팔의 불편감이다 [4]. RLS의 진단 기준은 1960년대에 Ekbom이 발표한 광범위한 진단 기준에서 지속적으로 발전해 왔다 [5].…”
Section: 서론unclassified